Collaboration in LIS education in the Asean region and beyond: issues and trends - Khoo, Christopher S. G. (2014)
The paper describes the author’s experience in regional collaboration activities in LIS education. The author found that networks and relationships formed through organizing and participating in conferences and workshops provide a basis for regional collaborative activities. A taxonomy of collaboration in LIS education is presented, listing the different types of collaborative activities that LIS schools can engage in, and the benefits that schools can derive from them. The main benefit of regional collaboration has been in giving students international and cross-cultural exposure, and in the training of PhD students. Continuing effort is needed to internationalize LIS education, as well as encourage research collaborations and formation of research clusters in the region.